Investigation of parameters influencing erosive wear using DEM - Akbar Jafari; Reza Abbasi Hattani (Friction)
Abstract The effects of several parameters on the erosive wear were studied using the discrete element method (DEM). The Finnie model was implemented using an open-source code. Regarding the time integration, the Gear algorithm was used, and to ensure the accuracy of the DEM results, a time-step sensitivity analysis was performed. The problem was modeled in two parts: first, the impact of a single particle on a surface was modeled, and then a more general model was prepared to examine the wear of surfaces under the flow of particles. The effects of the surface area, impact angle, speed, particle size, particle density, Young’s modulus, Poisson’s ratio, and restitution coefficient on the wear were studied numerically, and the results are discussed herein.